2007
DOI: 10.1186/gb-2007-8-9-r200
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and liver inflammation induced by increased dietary cholesterol intake: a combined transcriptomics and metabolomics analysis

Abstract: Background: Increased dietary cholesterol intake is associated with atherosclerosis. Atherosclerosis development requires a lipid and an inflammatory component. It is unclear where and how the inflammatory component develops. To assess the role of the liver in the evolution of inflammation, we treated ApoE*3Leiden mice with cholesterol-free (Con), low (LC; 0.25%) and high (HC; 1%) cholesterol diets, scored early atherosclerosis and profiled the (patho)physiological state of the liver using novel whole-genome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
187
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(205 citation statements)
references
References 36 publications
18
187
0
Order By: Relevance
“…49 Increased dietary cholesterol intake is associated with atherosclerosis. 50 The result of this study may suggest that men with a lower number of MetS components tend to abstain from eating eggs or cholesterol-rich foods. As a result, a doseresponse relationship between egg consumption and the number of MetS components was shown in our study.…”
Section: Dietary Factors and Metabolic Syndrome Components R Otsuka Ementioning
confidence: 77%
“…49 Increased dietary cholesterol intake is associated with atherosclerosis. 50 The result of this study may suggest that men with a lower number of MetS components tend to abstain from eating eggs or cholesterol-rich foods. As a result, a doseresponse relationship between egg consumption and the number of MetS components was shown in our study.…”
Section: Dietary Factors and Metabolic Syndrome Components R Otsuka Ementioning
confidence: 77%
“…They found elevated levels of xanthine and ascorbate in untreated mice which may be possible markers of plaque formation (Leo & Darrow, 2009). The interaction between diet and inflammation in promoting atherosclerosis has also been highlighted through metabolomic studies and Kleenmann (Kleemann et al, 2007) suggested that a high cholesterol intake lead to a switch in liver metabolism towards a pro-atherosclerotic state. Another recent example of how metabolomics can provide novel insights into inflammatory disease pathology was the observation that the metabolism of dietary lecithin by gut flora leads to the increased absorption and accumulation of choline derivatives which in turn promote cardiovascular disease (Wang et al, 2011) .…”
Section: Atherosclerosismentioning
confidence: 99%
“…Here we describe the impact of an LXR-agonist, T0901317, on the progression and regression of atherosclerosis in transgenic apoE*3Leiden (E3L) mice, a well-established mouse model for atherosclerosis (9,10). E3L mice are highly responsive to cholesterol-containing diets, resulting in strongly elevated plasma cholesterol and triglyceride levels, with a prominent increase in VLDL-and LDL-sized lipoprotein particles.…”
mentioning
confidence: 99%